Exosomes derived from chemically induced human hepatic progenitors inhibit oxidative stress induced cell death. Issue 9 (30th June 2020) - Hyung, Sujin; Jeong, Jaemin; Shin, Kyusoon; Kim, Ju Young; Yim, Ji‐Hye; Yu, Chan Jong; Jung, Hyun Suk; Hwang, Kyung‐Gyun; Choi, Dongho; Hong, Jong Wook
Abstract: The emerging field of regenerative medicine has revealed that the exosome contributes to many aspects of development and disease through intercellular communication between donor and recipient cells. However, the biological functions of exosomes secreted from cells have remained largely unexplored. Here, we report that the human hepatic progenitor cells (CdHs)‐derived exosome (EXO hCdHs ) plays a crucial role in maintaining cell viability. The inhibition of exosome secretion treatment with GW4869 results in the acceleration of reactive oxygen species (ROS) production, thereby causing a decrease of cell viability. This event provokes inhibition of caspase dependent cell death signaling, leading to a ROS‐dependent cell damage response and thus induces promotion of antioxidant gene expression or repair of cell death of hypoxia‐exposed cells. Together, these findings show the effect of exosomes in regeneration of liver cells, and offer valuable new insights into liver regeneration. Abstract : Protective effect of hCdHs‐derived exosome against oxidative stress in hepatocyte. Exosomes were isolated from chemically induced human hepatic progenitors (hCdHs) by using 'H' method. hCdHs‐derived exosome (EXOhCdHs) has a beneficial effect on antioxidant activity of damaged hepatocytes.